Development and Evaluation of Computational Thinking Based Mathematics E-Comics for Enhancing Numeracy Skills in Junior High School Students - Gunawan; Azhyzhah Noer Utami; Ferry Ferdianto; Fauzi Mulyatna; Lukmanul Akhsani (Asian Journal of Interdisciplinary Research, 2026)
Numeracy skills are needed to understand, apply, interpret, and solve contextual and complex problems. This is necessary because the process of solving problems in mathematics requires computational thinking steps. Therefore, this research aims to produce computational thinking-based e-comics to improve numeracy skills with a focus on students in grade VII of Junior High School. A research and development (R&D) design with the ADDIE model consisting of various stages such as analysis, design, development, implementation, and evaluation was applied. The research population is seventh grade junior high school students and the sample used is two classes of seventh grade, each totaling 32 people. The evaluation stage applied a quantitative approach with a quasi-experimental design. One class as an experimental class implementing computational thinking-based e-comics learning while the other class as a control class with interactive PowerPoint-assisted learning. The data collection methods used include interviews, student needs analysis questionnaires, validation and response questionnaires, numeracy test questions, and documentation. Moreover, the descriptive data retrieved from material and media experts were validated through validation sheets. Practicality analysis is also applied to teacher and student responses to the questionnaire sheets. The effectiveness analysis applies statistical procedures for normality tests, homogeneity, and statistical covariance analysis tests (ANCOVA). The results of expert validation showed an average of 84.79% which was categorized as valid. The practicality test also produced an average of 83% for the responses of the teachers and students which was classified as practical. Furthermore, the data showed normal and homogeneous categories. The ANCOVA test showed a significance value of 0.000 < 0.05. The research findings prove that the developed computational thinking-based e-comics effectively had a positive effect on improving students' numeracy skills. The research findings provide implications for innovation in enjoyable learning processes and teacher professional development.